Custom psychosurgery. Issue 578 (December 1973) - Turner, Eric
Abstract : It seems fundamentally improbable that different mental symptoms and personality disorders should be relieved by one single form of operation on the brain. The present paper describes five operations which can be performed with benefit to different types of psychiatric abnormality; namely, unilateral temporal lobectomy, unilateral or bilateral temporal lobotomy, inferior quadrant pre-frontal leucotomy, paramedian frontal leucotomy and posterior cingulectomy. The symptoms that represent an indication for these various operations and the results of the operations on the symptom complexes are described. The proposition is put forward that only operations suitable for the precise psychiatric diagnosis should be used. A new form of analysis of sphenoidal lead examinations is described which is of primary importance in conjunction with psychiatric examination in deciding which operation a particular patient would or would not benefit from. A concept of diencephalic instability is introduced in connection with this EEG analysis to supplement the usual concept of centrencephalic epilepsy. Diencephalic instability as defined here seems to respond specifically to paramedian lobotomy, provided of course the clinical condition justifies such a step.